Deodorizing materials

A deodorant material made from incineration ash and cement, processed to create a porous structure, effectively adsorbs both dry and wet gases, addressing the limitations of existing deodorants in handling wet gases.

JP7650457B2Active Publication Date: 2025-03-25KOBE UNIV +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021010007
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-27
Filing Date
2021-01-26
Publication Date
2025-03-25
Estimated Expiration
2041-01-26

AI Technical Summary

Technical Problem

Existing deodorants are ineffective in removing wet gases, which are commonly encountered in various industrial and environmental settings, whereas they can effectively adsorb dry gases.

Method used

A deodorant material composed of a mixture of incineration ash and cement, which is granulated, cured, and calcined to create a porous structure capable of adsorbing both dry and wet gases.

Benefits of technology

The deodorant material achieves high adsorption performance for both dry and wet gases, including hydrogen sulfide, methylmercaptan, ammonia, and trimethylamine, with a removal rate of 99% or more in both states.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007650457000005
    Figure 0007650457000005
  • Figure 0007650457000006
    Figure 0007650457000006
  • Figure 0007650457000007
    Figure 0007650457000007
Patent Text Reader

Abstract

To provide a deodorization material that can be applied to a gas in a wet condition as well as a gas in a dry condition.SOLUTION: This invention relates to a deodorization material containing incinerated ash and cement.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a deodorant material. [Background technology]

[0002] Activated carbon, acid-impregnated carbon, alkali-impregnated carbon, etc. have been used as deodorizing materials for malodorous gases for some time. However, these are very expensive because the manufacturing process is complicated. Therefore, studies are being conducted on the inexpensive recycling of coal incineration ash (coal ash) generated by electric power companies, which has traditionally been treated as industrial waste and has rarely been used.

[0003] Patent Document 1 describes that a deodorizer containing P-type zeolite produced by heating and crystallizing coal ash in an alkaline aqueous solution has a deodorizing effect on ammonia, hydrogen sulfide, and the like. Here, the deodorizing effect was observed in Patent Document 1 for dry gas, and Patent Document 1 does not describe whether the adsorbent can deodorize wet gas. Wet gas is generated from various business forms such as septic tanks, sewage treatment plants, refineries, biomass plants, industrial waste treatment plants, geothermal power plants, various pipelines, building pits, diesel engines and generators, methane fermentation plants, chemical plants, industrial complexes, and plating plants, and its removal is required. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 2-198630 Summary of the Invention [Problem to be solved by the invention]

[0005] In this situation, the problem to be solved by the present invention is to provide a deodorizing material that can be applied not only to dry gas but also to wet gas. [Means for solving the problem]

[0006] As a result of intensive research by the inventors to develop a deodorizing material that can be applied to not only dry gas but also wet gas, they discovered that by using a mixture containing incineration ash and cement as a deodorizing material, both dry gas and wet gas can be adsorbed and removed. The present invention was completed based on this finding.

[0007] That is, the present invention is as follows. Section 1. A deodorizing material containing incineration ash and cement. Section 2. 2. The deodorizing material according to item 1, wherein the incineration ash is coal ash. Section 3. 3. The deodorizing material according to item 1 or 2, which is porous. Section 4. 4. The deodorizing material according to any one of items 1 to 3, wherein the target of the deodorizing material is a gas in a wet state. Section 5. 5. The deodorizing material according to any one of items 1 to 4, wherein the target of the deodorizing material is one or more selected from the group consisting of hydrogen sulfide, methyl mercaptan, ammonia, and trimethylamine. Section 6. A method for producing a deodorizing material, comprising granulating incineration ash and cement using a solvent. Section 7. 7. A method for producing a deodorant material according to item 6, wherein after granulation, the granulated material is cured and then fired. Section 8. 8. The method for producing a deodorant material according to item 7, wherein the temperature during the firing is 500 to 800°C. Section 9. 8. The method for producing a deodorant material according to item 7, wherein the temperature during the firing is 600 to 800°C. Section 10. A deodorant material produced by the method for producing a deodorant material according to any one of items 6 to 9 above. Section 11. A deodorizing method comprising contacting the deodorizing material according to any one of items 1 to 3 with a wet gas. Effect of the Invention

[0008] The deodorizing material of the present invention is capable of adsorbing and removing not only dry gas but also wet gas. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram of an apparatus used in the hydrogen sulfide gas adsorption test of Test Example 1. [Diagram 2] FIG. 2 is an example of a graph showing the saturated adsorption amount of hydrogen sulfide gas. [Diagram 3] FIG. 3 is a graph showing the saturated adsorption amounts of hydrogen sulfide gas in the dry and wet states of Samples 1 to 3. [Figure 4] FIG. 4 is a schematic diagram of the apparatus used in the malodor adsorption test in Test Example 2. [Diagram 5] FIG. 5 is a graph showing the removal rates of the four major malodors of Sample 3 in a dry state and in a wet state. [Figure 6] FIG. 6 is a graph showing the saturated adsorption amount of hydrogen sulfide gas and the BET specific surface area of ​​Samples 4 to 12 in a dry state and in a wet state. [Figure 7] FIG. 7 is a graph showing the results of measuring the strength (point load) of Samples 4 to 12 and zeolite. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] 1. Deodorizing materials The deodorizing material includes incineration ash and cement. By mixing the incineration ash and cement, a mixture with a dense structure and improved strength is obtained. The obtained mixture can adsorb and remove not only dry gas but also wet gas.

[0011] Incineration ash contains silica (SiO 2 ) and alumina (Al 2 O 3) is not particularly limited, so long as it contains the above-mentioned. Examples of incineration ash include waste incineration ash such as urban waste, wood chips, tire chips, paper sludge, sewage sludge, and biomass; incineration ash such as coal, solid waste fuel, and paper or plastic solid fuel. These may be used alone or in combination of two or more.

[0012] Among these, coal incineration ash (coal ash) generated by electric power companies is preferably used because it contains less impurities such as arsenic. As the coal ash, so-called fly ash discharged from thermal power plants using coal as fuel can be used. Fly ash is made up of silica (SiO 2 ) and alumina (Al 2 O 3 ) as the main component, and other components include oxides of iron, calcium, magnesium, sulfur, sodium, potassium, manganese, etc. (e.g., Fe 2 O 3 , CaO, MgO, SO 3 , Na 2 OK 2 Fly ash is produced in large quantities during the combustion of coal, and since it is desirable to reuse it, it is useful as a raw material for the deodorizing material of the present invention.

[0013] The type of cement is not particularly limited, and examples thereof include common cements used in concrete production, such as Portland cement and alumina cement. From the viewpoint of environmental conservation, cement that does not leach toxic components into ocean, lake, and other water is preferable. One example of cement with low leaching of toxic components is blast furnace cement (particularly, type B blast furnace cement). It is preferable not to use Portland cement, which is called ordinary cement, that leachs a large amount of toxic hexavalent chromium, etc.

[0014] As described above, the deodorizing material of the present invention contains incineration ash and cement, but it is sufficient that the raw materials contain incineration ash and cement, and may include, for example, the raw materials "deodorizing material obtained from incineration ash and cement," "deodorizing material produced by reacting incineration ash and cement," etc. Since it is impossible or impractically difficult to specify at this time what components are contained in the "deodorizing material obtained from incineration ash and cement," the deodorizing material is described using a product-by-process claim.

[0015] The content of the incineration ash and cement contained in the deodorizing material is preferably 5 to 150 parts by mass, more preferably 10 to 30 parts by mass, and even more preferably 13 to 20 parts by mass of cement per 100 parts by mass of incineration ash. By setting the content of each component within the above range, a granulated material that can exhibit higher deodorizing performance can be obtained.

[0016] The deodorizing material is preferably a granulated material containing incineration ash and cement. The incineration ash contains silica (SiO 2 ) and alumina (Al 2 O 3 ), when mixed with cement, it reacts with the calcium hydroxide produced during the hydration of cement (porazon reaction) to produce calcium silicate hydrate, calcium aluminate hydrate, etc., resulting in a finer structure of the resulting mixture and improved strength. Therefore, it is preferable that the deodorizing material of the present invention is porous.

[0017] The deodorant of the present invention is used for removing malodorous gases. The malodorous gases to be removed by the deodorant of the present invention are not particularly limited as long as they are gases (vapors) that emit malodors (unpleasant odors), and examples of such gases include oxygen-containing compounds, nitrogen-containing compounds, sulfur-containing compounds, and hydrocarbons. The gases may be in a dry or wet state.

[0018] Examples of oxygen-containing compounds include aldehyde compounds such as acetaldehyde, propionaldehyde, n-butyraldehyde, and isobutyraldehyde; alcohol compounds such as isobutanol; ester compounds such as ethyl acetate; ketone compounds such as methyl isobutyl ketone and diacetyl; and organic carboxylic acid compounds such as propionic acid, n-butyric acid, n-valeric acid, and isovaleric acid. Examples of the nitrogen-containing compound include ammonia and amine compounds such as trimethylamine. Examples of sulfur-containing compounds include methyl mercaptan, hydrogen sulfide, methyl sulfide, and methyl disulfide. Examples of the hydrocarbon include aromatic hydrocarbons such as toluene, styrene, and xylene.

[0019] The BET specific surface area of ​​the deodorizing material is 5m 2 / g or more is preferable, and 10m 2 / g or more is more preferable, and 20m 2 / g or more is more preferable. 2 By having a specific surface area of ​​100 m / g or more, the material can exhibit high adsorption performance against malodorous gases. 2 / g.

[0020] The deodorizing material is preferably particulate. Its particle size is not limited and can be appropriately set according to its application, use conditions (deodorizing conditions), etc. For example, the average particle size may be about 1 to 30 mm. From the viewpoint of handling, it is preferably 3 mm or more, more preferably 5 to 20 mm. In order to increase the surface area from the viewpoint of adsorption performance against malodorous gases, it is even more preferable that the average particle size is 5 to 10 mm. These particle size adjustments can be performed by using known methods such as classification and pulverization. In addition, the particle shape of the deodorizing material is not limited and may be any form such as spherical, flake, or irregular. In particular, from the viewpoint of packing into a fixed bed (column, etc.), liquid flowability, etc., it is preferable that the shape is spherical.

[0021] The adsorbent of the present invention not only has an adsorption effect on dry gas, but also has an adsorption effect on wet gas. Therefore, since the deodorizing material of the present invention is inexpensive and has an excellent adsorption effect on wet gas, it can be used as a deodorizing material in, for example, hot springs, geothermal power plants, oil refineries, temporary toilets, and distributed wastewater treatment devices (such as septic tanks) where the exhaust humidity is close to 100%, etc.

[0022] 2. Manufacturing method of deodorant The deodorizing material of the present invention is obtained by granulating incineration ash and cement using a solvent. As long as a granulated material containing incineration ash and cement can be obtained, the manufacturing method is not particularly limited. The solvent used for granulation is not particularly limited as long as it can form a granulated material. The solvent preferably contains water, and water (tap water, distilled water, ion-exchanged water, etc.), seawater, brackish water, groundwater, river water, sodium chloride aqueous solution, lithium nitrite aqueous solution, etc. can be used. The amount of the solvent used can be appropriately adjusted so that a granulated material is formed according to the blending amount of each raw material.

[0023] As a production method, for example, a method of mixing incineration ash with cement, adding a solvent (for example, water) to the obtained mixture, and granulating the mixture can be mentioned.

[0024] The mixing ratio of the incineration ash and the cement is preferably 5 to 150 parts by mass, more preferably 10 to 30 parts by mass, and further preferably 13 to 20 parts by mass of cement per 100 parts by mass of the incineration ash.

[0025] The obtained granules are preferably cured and then fired. The granules are cured to make them porous, and the hydrophilicity of the surface of the granules can be reduced by firing the granules. This makes it possible to obtain an adsorbent that can adsorb dry gases and has the same adsorption performance for wet gases as for dry gases (adsorption performance for wet gases is not reduced). The curing conditions can be appropriately adjusted according to the temperature, humidity, etc. As an example of curing, natural drying for several days to several weeks can be mentioned. The temperature during firing (firing temperature) can be about 300 to 1000°C. From the viewpoint of improving the strength of the granules after firing and the adsorption performance for wet gases, 300 to 900°C is preferable, 500 to 800°C is more preferable, 600 to 800°C is even more preferable, and 600 to 700°C is particularly preferable.

[0026] The firing atmosphere is not particularly limited, and may be, for example, any of an oxidizing atmosphere (air), a reducing atmosphere, an inert gas atmosphere, etc. The firing time can also be appropriately adjusted depending on the firing temperature, etc.

[0027] The obtained sintered body is in a particulate form and can be used as a deodorizing material as it is. It can also be used as a deodorizing material after being crushed, classified, or otherwise processed as necessary. As shown in the following examples, the sintered body obtained through the firing process has an excellent removal effect against all of the four major odors, namely hydrogen sulfide, methyl mercaptan, ammonia, and trimethylamine, in both dry and wet states. Therefore, it can be suitably used as a deodorizing material against various odorous gases, regardless of whether it is in a dry or wet state. EXAMPLES

[0028] The present invention will be described in more detail below with reference to examples, but the technical scope of the present invention is not limited to these examples.

[0029] Example 1 Coal ash and blast furnace cement were mixed in a mass ratio of 87:13, and water equivalent to 20% of the mass of the resulting mixture was added. Granules with a diameter of approximately 10 to 20 mm were produced in a granulator under the conditions of a granulation pan angle of 30 to 60 degrees and 35 to 50 rpm. The granules were cured for 4 weeks to harden (become porous). Water was sprayed onto the granules every day for the first 7 days. From the resulting granules, granules with a diameter of 3 to 5 mm were selected using a sieve and designated as sample 1.

[0030] Examples 2 and 3 Granules with a diameter of about 10 to 20 mm were crushed with a hammer and sieved to collect only those with a diameter of 3 to 5 mm. These were placed on an evaporation dish with as little overlap as possible, placed in a muffle furnace, and fired in the muffle furnace for 3 hours. The one fired at 500°C was designated sample 2, and the one fired at 700°C was designated sample 3.

[0031] Test Example 1 For the above samples 1 to 3, an adsorption test of hydrogen sulfide gas (in a dry state and in a wet state) was carried out. FIG. 1 shows a schematic diagram of the apparatus used in the adsorption test of hydrogen sulfide gas. Deoxygenated air was passed through a saturated sodium sulfide solution to which sodium sulfide crystals had been added so that they remained as crystals in the solution, generating hydrogen sulfide gas. When deoxygenated air was continuously passed through the saturated sodium sulfide solution, the pH increased and hydrogen sulfide gas became more likely to dissolve in the solution, so 10% hydrochloric acid was dropped every 3 minutes to maintain the pH on the acidic side and stabilize the hydrogen sulfide gas. As the deoxygenated air, a plastic bag containing a large amount of oxygen absorber (Ageless (registered trademark), manufactured by Mitsubishi Gas Chemical Co., Ltd.) together with the required amount of air was used overnight in a sealed plastic bag. The deoxygenated air in the plastic bag was passed through the saturated sodium sulfide solution at 0.3 L / min with a blower, and hydrogen sulfide gas was sent to a column filled with an adsorbent at a rate of 0.3 L / min. A gas collection bag was provided at the rear of the column, and the concentration of hydrogen sulfide gas collected in the collection bag for 3 minutes was measured with a gas detector. A separate collection bag was provided in front of the column, and the concentration of hydrogen sulfide gas flowing into the column was appropriately measured. The hydrogen sulfide gas adsorption amount was calculated by multiplying the difference in hydrogen sulfide gas concentration before and after passing through the column by the amount of air passed through. The value obtained by integrating the hydrogen sulfide gas adsorption amount for each measurement until the end of the test was taken as the saturated adsorption amount. Here, for example, the criteria for saturated adsorption will be explained with reference to Table 1 and the graph shown in Figure 2. The adsorption was judged to be saturated when the hydrogen sulfide gas concentration after passing through the column exceeded 100 ppm for three consecutive points (42 to 45 minutes), and the saturated adsorption amount included the adsorption amount up to the third point where the hydrogen sulfide gas concentration exceeded 100 ppm.

[0032] [Table 1]

[0033] The column packed with the deodorizing material was made of processed polyvinyl chloride pulp and had a capacity of 35.3 mL (diameter 30 mm x length 50 mm). By using samples 1 to 3 as they are as adsorbents packed in the column, the adsorption performance for hydrogen sulfide gas in a dry state can be evaluated. On the other hand, by immersing each of samples 1 to 3 in tap water for 24 hours and draining the water (adsorbents in a wet state), the adsorption performance for hydrogen sulfide gas in a wet state can be evaluated. The adsorbents in a wet state are assumed to be in a steady state when the adsorbents are placed under high humidity conditions for a long period of time. The results are shown in Figure 3.

[0034] From Figure 3, it was found that sample 1 (coal ash granules that were not calcined) adsorbs hydrogen sulfide both in a dry state and in a wet state, but the amount of hydrogen sulfide adsorbed in the wet state is smaller than the amount of hydrogen sulfide adsorbed in the dry state. Sample 2 (coal ash granules calcined at 500°C) and sample 3 (coal ash granules calcined at 700°C), which were calcined, had hydrogen sulfide adsorption amounts in the wet state that were equal to or greater than those in the dry state, and sample 3, which was calcined at 700°C, in particular, had high hydrogen sulfide adsorption performance in both a dry state and a wet state.

[0035] Test Example 2 Next, a malodor adsorption test was conducted on sample 3 (baked at 700°C). First, a fermentation solution that generates a malodor was prepared. The composition of the fermentation solution is shown in Table 2 below. Note that MLSS (Mixed Liquor Suspended Solids) refers to the concentration of activated sludge in the aeration tank of the activated sludge process.

[0036] [Table 2]

[0037] Figure 4 shows a schematic diagram of the device used in the malodor adsorption test. Specifically, the fermented solution was heated to 55°C and fermented for 24 hours, and a blower with an aeration rate of 1.25 L / min was connected to the container containing the fermented solution. After the malodor generated from the container was passed through an empty column (dehumidification column), the malodor gas (target gas) was aerated through a column filled with a deodorizing material and a column not filled with an adsorbent. Gas collection bags were provided at the rear of the column filled with the deodorizing material and at the rear of the column not filled with the deodorizing material, and the concentration of the target gas was measured with a gas detector tube in each gas collection bag, and the removal rate was calculated by comparing the concentration difference. The capacity of each column was 600 mL (diameter 52 mm x length 300 mm), and the capacity of the deodorizing material was 500 mL. As the deodorizing material, sample 3 (in a dry state) and sample 3 moistened in the same manner as in Test Example 1 above were used. The target gas was hydrogen sulfide (H 2 S), methyl mercaptan (MM), ammonia (NH 3 The results are shown in Figure 5.

[0038] As shown in Figure 5, Sample 3 fired at 700°C showed a removal rate of 99% or more for the four major odors (hydrogen sulfide, methyl mercaptan, ammonia, and trimethylamine) in both dry and wet states. This shows that the deodorizing material obtained by firing at 700°C after granulation and curing has an excellent deodorizing effect not only on dry gases but also on wet gases.

[0039] Example 4 Coal ash and blast furnace cement were mixed in a mass ratio of 87:13, and water equivalent to 20% of the mass of the resulting mixture was added. The angle of the granulating pan in a granulator was set to 30-60 degrees, and the speed was set to 35-50 rpm to produce granules with a diameter of approximately 10-20 mm. The granules were cured for 4 weeks to harden (become porous). Water was sprayed onto the granules every day for the first 7 days. Sample 4 was selected from the resulting granules with a diameter of 3-5 mm using a sieve.

[0040] Examples 5 to 12 Granules with a diameter of about 10 to 20 mm were crushed with a hammer, and only those with a diameter of 3 to 5 mm were collected by sieving. They were placed on an evaporating dish so as not to overlap as much as possible, put into a muffle furnace, and fired in the muffle furnace for 3 hours. The firing was carried out at temperatures of 300 °C, 400 °C, 500 °C, 600 °C, 700 °C, 800 °C, 900 °C, or 1000 °C. The sample fired at 300 °C was designated as sample 5, the one at 400 °C as sample 6, the one at 500 °C as sample 7, the one at 600 °C as sample 8, the one at 700 °C as sample 9, the one at 800 °C as sample 10, the one at 900 °C as sample 11, and the one at 1000 °C as sample 12.

[0041] Test Example 3 For the above samples 4 to 12, an adsorption test of hydrogen sulfide gas (dry and wet states) was carried out in the same manner as in Test Example 1. The adsorption test was performed 3 times for each sample, and the average value and standard deviation were calculated. Also, the BET specific surface area and strength of the samples were measured by the methods shown below. The results of the adsorption test and BET specific surface area are shown in Table 3 and Figure 6, and the results of the strength are shown in Table 4 and Figure 7.

[0042] <Strength> For the above samples 4 to 12, the point load was measured with a load measuring instrument (manufactured by IMADA Co., Ltd., digital force gauge S-3).

[0043] <BET specific surface area> For the above samples 4 to 12, the BET specific surface area by nitrogen gas was measured with an automatic specific surface area measuring device (manufactured by Shimadzu Corporation, Gemini VII2390). The measurement was performed 5 times for each sample, and the average value and standard deviation were calculated. Also, the point load of the zeolite used as the adsorbent was measured in the same manner. Note that as the zeolite, Matrix (granular, particle size 10 mm) manufactured by Seachem was used.

[0044]

Table 3

[0045]

Table 4

[0046] result From Table 3 and Figure 6, it was found that Samples 5 to 12, which were fired at temperatures of 300 ° C to 1000 ° C, have similar hydrogen sulfide adsorption amounts in a dry state and a wet state, although there is a difference in the adsorption amount. Sample 5 (coal ash granules fired at 300 ° C), Sample 6 (coal ash granules fired at 400 ° C), Sample 7 (coal ash granules fired at 500 ° C), Sample 8 (coal ash granules fired at 600 ° C), Sample 9 (coal ash granules fired at 700 ° C), and Sample 10 (coal ash granules fired at 800 ° C) had higher hydrogen sulfide adsorption amounts in a wet state than Sample 4 (coal ash granules not fired). In particular, it was found that sample 8 (coal ash granules fired at 600°C) and sample 9 (coal ash granules fired at 700°C) had high hydrogen sulfide adsorption performance both in a dry state and in a wet state. In addition, sample 4 (coal ash granules that were not fired), sample 5 (coal ash granules fired at 300°C), sample 6 (coal ash granules fired at 400°C), sample 7 (coal ash granules fired at 500°C), sample 8 (coal ash granules fired at 600°C), and sample 9 (coal ash granules fired at 700°C) all had a BET specific surface area of ​​5 m 2 / g or more, it can be said that the material exhibits high adsorption performance against malodorous gases.

[0047] From Table 4 and Figure 7, it can be seen that sample 7 (coal ash granules fired at 500°C), sample 8 (coal ash granules fired at 600°C), sample 9 (coal ash granules fired at 700°C), sample 10 (coal ash granules fired at 800°C), sample 11 (coal ash granules fired at 900°C), and sample 12 (coal ash granules fired at 1000°C) all had higher strength than zeolite. This shows that a deodorizing material with sufficient strength can be obtained by firing the coal ash granules at a temperature of 500°C or higher.

[0048] From the above results, it was found that by firing coal ash granulated material containing coal ash and cement at 500°C to 800°C, particularly 600°C to 700°C, a deodorizing material with high adsorption performance for gases in both dry and wet states and sufficient strength can be obtained.

Claims

1. A deodorizing material containing incineration ash and cement, It has been baked, and A deodorizing material having a BET specific surface area of ​​5 m 2 / g to 100 m 2 / g.

2. 2. The deodorizing material according to claim 1, wherein the incineration ash is coal ash.

3. The deodorizing material according to claim 1 or 2, which is porous.

4. The deodorizing material according to any one of claims 1 to 3, wherein the target of the deodorizing material is a gas in a wet state.

5. The deodorizing material according to any one of claims 1 to 4, wherein the target of the deodorizing material is one or more selected from the group consisting of hydrogen sulfide, methyl mercaptan, ammonia, and trimethylamine.

6. The incineration ash and cement are granulated using a solvent, A method for producing a deodorizing material, comprising granulating the granulated material, curing the granulated material, and then firing the granulated material, The firing temperature is 300 to 700° C., A method for producing a deodorizing material, wherein the target of the deodorizing material is one or more selected from the group consisting of hydrogen sulfide, methyl mercaptan, ammonia, and trimethylamine.

7. The method for producing a deodorizing material according to claim 6, wherein the temperature during the firing is 500 to 700°C.

8. The method for producing a deodorizing material according to claim 6, wherein the temperature during the firing is 600 to 700°C.

9. A method for manufacturing a deodorizing material as described in claim 6, wherein the curing is a process of curing by natural drying.

10. A deodorizing method comprising contacting the deodorizing material according to any one of claims 1 to 5 with a wet gas.

Citation Information

Patent Citations

  • Sludge deodorant and sludge deodorization method

    CN107324727A

  • Deodorant for malodorous material

    JP1990198630A

  • Deodorant and deodorizing device

    JP1996173514A

  • Porous ceramic particle and its production process

    JP2002241183A

  • Air ion generating molding and ion generator

    JP2007105430A